2015
DOI: 10.1007/s12594-015-0256-x
|View full text |Cite
|
Sign up to set email alerts
|

Seismotectonic and Seismicity Analysis of the Damghan Region, Iran

Abstract: This paper deals with seismotectonic and seismicity analysis of the Damghan region, the central part of Semnan province, northeast of Iran. Seismotectonic and seismicity maps s well as active faults of the region were introduced and an earthquake catalogue of the studied area (up to 150 km radiuses) was prepared. This study addresses the main historical and instrumental earthquakes and their causative faults. Available seismic data were normalized by means of the time normalization technique that resulted in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Literature review showed that there are four active faults passing underneath Damghan. One of these faults, called Astaneh, on the northwest of Damghan, accounted for the sixth largest earthquake in the world, measuring 7.6 M and killing 200.000 (17). In previous studies which investigated the natural disasters in Iran, due to numerous faults and high seismicity in the country, earthquake is considered as the biggest hazard in the country (2,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature review showed that there are four active faults passing underneath Damghan. One of these faults, called Astaneh, on the northwest of Damghan, accounted for the sixth largest earthquake in the world, measuring 7.6 M and killing 200.000 (17). In previous studies which investigated the natural disasters in Iran, due to numerous faults and high seismicity in the country, earthquake is considered as the biggest hazard in the country (2,24).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand Damghan is faced with the heavy winds and extreme weather in the most days of a year because it is surrounded by the Alborz mountains range from the north. Also, most of population has low to middle income and access to HCFs for receiving the health care services at time of disasters and emergencies (17). In regard to locate Damghan County on the active faults with high seismic background, exposed to risk of severe hurricanes, accident road, social vulnerability and lack of facilities, it is expected much population refer to HCFs for receiving services at time of disasters and emergencies.…”
Section: Preparedness Capacity Includes Human Resources Facilities mentioning
confidence: 99%